Análise das circunstâncias econômicas da prática criminosa no Estado do Paraná: estudo de caso nas penitenciárias estadual, central e feminina de Piraquara - Borilli, Salete Polonia (2005)
The objective of this work consists of an analysis of the economic crime of Paraná State through a case study developed in the Central (PCP), Feminine (PFP) and State (PEP) Penitentiaries in the city of Piraquara, based on a primary data collected from questionnaires/interviews which were applied to previously judged and condemned defendants for economic crimes. In this research, the hypothesis that the criminals migration to illegal activities was in the hope of earning more than the risks of the activity was not rejected. The option for the practice of crime of economic nature is a rational and individual one, with or without the influence of others, in face of the perception of costs and benefits such as those made by individuals in relation to others decisions of economic nature. The offenders make individual decisions when the results of criminal action fulfill their interest well or better than the collective action. The relation crime-unemployment did not prove to be so strong in this research, since the majority of the respondents were working when the practice of crime happened. The association of criminality with low level of education was confirmed; the majority of respondents have got only Educação Fundamental (first to four grades), what suggests that high levels of education and better jobs (well payment) can restrict or to retrain the criminality. We observed that more audacious criminal practices besides high levels of organization and planning are essential requisites to these tasks. The principal crime realized were: robbery deal in drugs, fraud, armed-robbery, abduction and extortion that the majority were realized by white young men from the State of Paraná, member of a religious community and having a family. The choice of the type of crime to be realized and the victims, was determined in function of material interest and possible earnings. The main personal motivation to act illegally vis-à-vis to legal was: the induction of friends, the greediness, to maintain the vice, the inconsequence and the wish of adventure, the difficult of money and the idea of easy earnings. The main factors of failure were: the informer, the police's action and their own failure; though, the failure do not refer to the punishment, but to the economic gains not reached. The research revealed that for most of respondents the illegal activity results in some degree of success and for a significant number the economic return was the expected, what justify the great number of relapsing. Finally, for the majority of them the Justice System was considered as insufficient to impede the criminal activity.